Promises i made my mother - Haskell, Sam, 1955-; Rensin, David; Romano, Ray; Random House Audio (New York : Random House Audio, 2009)
In this inspiring memoir full of touching stories and amusing anecdotes, Haskell reveals how he kept his pledge to his mother to live a decent life--even in the shark-infested waters of Hollywood, where he handled the hottest stars and packaged the highest-rated shows--by refusing to become the cliché of an amoral agent
Title from container
Keywords: Haskell, Sam, -- 1955-; Theatrical agents -- United States -- Biography; Executives -- United States -- Biography